Analysis of Personality, Suicide, and Self‐Injury in Emerging Adulthood. Issue 1 (14th April 2020) - La Guardia, Amanda C.; Cramer, Robert J.; Bryson, Claire N.; Emelianchik‐Key, Kelly
Abstract : Nonsuicidal self‐injury (NSSI) is a maladaptive coping strategy that is of significant clinical concern for behavioral health professionals in college settings. Relationships between NSSI, acquired capability for suicide, interpersonal cognitions, and five‐factor model personality traits were assessed in a survey‐based study that included 192 young adults in a college setting. Results indicated that those with an affirmative suicide attempt history, greater acquired capability for suicide, and elevated neuroticism had an increased likelihood of lifetime NSSI.